Laparoscopic versus Open Surgery of Liver Hydatid Cysts in Mosul Center - W. Ahmed, Noor; K. Alhadidi, Salih; H. AL Ali, Mohammed (Scientific Journal of Medical Research, 2024)
Background: Liver hydatid cysts are common chronic parasitic infections in Mosul city caused mostly by the tapeworm Echinococcus granulosus and less commonly Echinococcus multilocularis may need to be surgically treated to prevent complications of the disease as rupture, pressure symptoms on adjacent organs and anaphylaxis, for surgical treatment there are laparoscopic and open approaches. Aim of study: To compare the results of both laparoscopic and open approaches in liver hydatidosis treatment. Patients and methods: A prospective clinical trial study was conducted at the Department of Surgery at Mosul Teaching Center, the sample size is 62 cases; 2 cases of ruptured hydatid cysts were excluded, so the sample became 60 cases divided into two groups (30 case laparoscopic approach( group A) and 30 case open approach (group B), data analyzed by SPSS program for statistical analysis from April 2022 to April 2023. Results: The study showed that the laparoscopic approach for liver hydatid cysts is associated with shorter operative time, faster recovery, shorter hospital stay, less post-operative pain, better cosmetic result and less wound infection with significant statistical differences between the two approaches as p values corresponding to (0.000 for operative time, recovery period, length of hospital stay and cosmetic result with 0.024 for post-operative pain and wound infection. Conclusion: For the surgical management of liver hydatid disease, both open and laparoscopic approaches are used; however, the laparoscopic approach is currently more popular and has advantages over the open approach. In the coming years, it is anticipated that this approach will be the primary method for surgical treatment of liver hydatid cysts. We would like to suggest carrying out additional research on this topic using larger sample sizes and longer follow-up periods.